2006
DOI: 10.1016/j.ejvs.2005.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Statins are Associated with a Reduced Infrarenal Abdominal Aortic Aneurysm Growth

Abstract: Statins appear to be associated with attenuation of AAA growth, irrespective of other known factors influencing aneurysm growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
184
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(204 citation statements)
references
References 38 publications
12
184
3
4
Order By: Relevance
“…Some studies used CT as well as US. 22,29,33 Most of these studies included aortic diameters from 30 mm (at baseline), except three studies, which reported from either 25 mm 31,35 or 28 mm. 13 Not all studies restricted their reporting to the aneurysm diameter range of interest (3.0-5.5 cm) and in some instances substudies were identified, which reported on a more restricted range.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies used CT as well as US. 22,29,33 Most of these studies included aortic diameters from 30 mm (at baseline), except three studies, which reported from either 25 mm 31,35 or 28 mm. 13 Not all studies restricted their reporting to the aneurysm diameter range of interest (3.0-5.5 cm) and in some instances substudies were identified, which reported on a more restricted range.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data. 31 Aneurysm growth was the primary outcome measure in 10 of the 15 studies. Overall, there were 7630 persons included in these 15 studies (although the two Spanish studies 32,33 may have included some duplicated patients).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a meta-analysis by Li et al [17] of six epidemiological studies also showed that respiratory disease was a risk factor for AAA (OR, 1.36; 95% CI, 1.19 to 1.55). However, the eight currently available studies [15,[28][29][30][31][32][33][34]] demonstrated a lack of association between COPD with AAA growth. These fi ndings, including the results of the present review (the same comorbidity is positively associated with AAA presence but not or even negatively associated with AAA growth), suggest that accelerated mechanisms regarding the expansion of an existing AAA may be diff erent from those regarding the initial formation of an AAA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an observational study including 130 patients follow up for 2 years, no aneurysm expansion was observed in 75 patients taking statins (Baxter et al,2008). Other studies have been also suggested that the aneurysm expansion rate was decreased in the patients who were taking statins compared with those not taking statins (Schouten et al,2006). Another important query is about the molecular pathways by which statins may affect AAA growth.…”
Section: Statinsmentioning
confidence: 99%